2003
DOI: 10.1242/dev.00202
|View full text |Cite
|
Sign up to set email alerts
|

Localized JAK/STAT signaling is required for oriented cell rearrangement in a tubular epithelium

Abstract: SUMMARYLocalized JAK/STAT signaling is required for oriented cell rearrangement in a tubular epithelium

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 62 publications
6
59
1
1
Order By: Relevance
“…Furthermore, expression of an activated form of HOP in a large number of anterior follicle cells led to a dramatic increase in the level of accumulation of STAT protein in those cells. This observed increase in STAT protein in response to excess JAK activity is consistent with previous studies that showed that STAT protein levels are dramatically reduced, when compared with wild type, in upd, hop and dome (also called mom) mutant embryos (Chen et al, 2002), and are upregulated upon overexpression of UPD and HOP TUM (Johansen et al, 2003). Thus, both the subcellular localization and the overall level of STAT protein respond to the level of activity of the pathway.…”
Section: Requirement For Continuous Stat Activity Throughout Border Csupporting
confidence: 90%
“…Furthermore, expression of an activated form of HOP in a large number of anterior follicle cells led to a dramatic increase in the level of accumulation of STAT protein in those cells. This observed increase in STAT protein in response to excess JAK activity is consistent with previous studies that showed that STAT protein levels are dramatically reduced, when compared with wild type, in upd, hop and dome (also called mom) mutant embryos (Chen et al, 2002), and are upregulated upon overexpression of UPD and HOP TUM (Johansen et al, 2003). Thus, both the subcellular localization and the overall level of STAT protein respond to the level of activity of the pathway.…”
Section: Requirement For Continuous Stat Activity Throughout Border Csupporting
confidence: 90%
“…For UAS/GAL4-induced ectopic expression, embryos were grown at 28°C using the lines UAS-p35 (Zhou et al, 1997), UAS-bin #35 (Zaffran et al, 2001), byn-GAL4 UAS-GFP (Johansen et al, 2003) (from J. Lengyel, UCLA, USA), bap3-GAL4 (Lee et al, 2003), 2xPE-twi-GAL4;24B-GAL4 (Reim and Frasch, 2005), UAS-HLH54F-IR (P{KK103428}v103965) and UAS-da-IR (P{GD4440}v51300) (both from VDRC, Vienna, Austria) (Dietzl et al, 2007).…”
Section: Drosophila Strainsmentioning
confidence: 99%
“…all JAK/STAT functions analysed (Brown et al, 2001;Ghiglione et al, 2002;Johansen et al, 2003), we suspected that it might be forming homo-dimers. To test whether homodimerisation of DOME occurs in Drosophila, and to find how it is controlled during development, we decided to use a technique that would allow us to observe dimerisation in situ.…”
Section: Introductionmentioning
confidence: 99%